If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 3 + -1b Solving 15 = 3 + -1b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add 'b' to each side of the equation. 15 + b = 3 + -1b + b Combine like terms: -1b + b = 0 15 + b = 3 + 0 15 + b = 3 Add '-15' to each side of the equation. 15 + -15 + b = 3 + -15 Combine like terms: 15 + -15 = 0 0 + b = 3 + -15 b = 3 + -15 Combine like terms: 3 + -15 = -12 b = -12 Simplifying b = -12
| 9x-5+10(x+3)=40 | | 1008=2x^2+8x-1072 | | 8y-5=2y+7 | | 4a-6=2a-12 | | 7x+2(6x-4)=-141 | | (x-3)(2x+-1)=0 | | 6x-11=7x+5 | | 2z^3+z^2=15z | | 9x-7=-12 | | 3x^2-12x+9=1 | | 1a-15=48-3 | | 6x+9=29-4x | | x^2-4x=x^2-2x | | 32-11x=142 | | x^2-3x+x=x^2-2x | | 2(3x+5)=5(x-7) | | 9+a=-42 | | 54=8-j | | y=x(4-2x)(5-2x) | | 10z+3=12-7 | | y=6e-16*x^6 | | 7x^2+75x+50=0 | | 900-7x=95 | | 7T+4=4+-11 | | 4x-1.4=.6 | | Y+11=1.4(x-6) | | 3T-9=T+11 | | -Y-2X+9Y= | | 2(7x-55)=7x-20-5 | | 5x-1.9=2.6 | | 16x-7x+26= | | 2(-4+3)x=2(-2) |